Lethal penetrating stab injury to the vertebral artery: A case report with review of literature - Sarkari, Avijit; Singh, Pankaj; Mahapatra, Ashok (Asian Journal of Neurosurgery, 2016)
The vertebral arteries are rarely injured in penetrating neck trauma due to their deep location in the foramen transversarium. These injuries in isolation are not associated with neurological deficits or ischemic changes on radiology as the collaterals are usually sufficient. We report a case of fatal unilateral vertebral artery stab injury leading to bilateral cerebellar and brainstem infarction. The carotid Doppler ruled out the presence of any carotid artery injury. Life-threatening injuries are possible in the presence of hypoplastic contralateral vertebral artery or inadequate flow from the anterior circulation not making up for the deficit. This emphasizes that thorough evaluation and timely management of suspected injuries to even a single vertebral artery should be undertaken.
Keywords: Brainstem injury; stab wound; stroke; vertebral artery injury